2013
DOI: 10.1364/oe.21.006101
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-on-insulator spectrometers with integrated GaInAsSb photodiodes for wide-band spectroscopy from 1510 to 2300 nm

Abstract: Abstract:We present a silicon-on-insulator (SOI) based spectrometer platform for a wide operational wavelength range. Both planar concave grating (PCG, also known as echelle grating) and arrayed waveguide grating (AWG) spectrometer designs are explored for operation in the short-wave infrared. In addition, a total of four planar concave gratings are designed to cover parts of the wavelength range from 1510 to 2300 nm. These passive wavelength demultiplexers are combined with GaInAsSb photodiodes. These photodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 11 publications
(8 reference statements)
1
68
0
Order By: Relevance
“…Finally the efficiency of the diffraction grating itself could not be estimated at this stage due to the several possible sources of loss in the whole spectrometer previously mentioned, but is expected to be high from the precise FDTD estimation. For comparison, other CDG spectrometers have an average efficiency of -3.2 dB, with a range from -5.0 dB to -1.6 dB, as claimed, 14,[19][20][21]24,25,29,30,[33][34][35] and have an average channel uniformity (over a band equivalent to 30 nm at 1550 mn) of 0.9 dB, with a range from 1.5 dB to 0.2 dB. 14,[19][20][21]24,25,29,30,[33][34][35] This places the present spectrometer within the state of the art for efficiency and at a high level for uniformity.…”
Section: Optical Testingmentioning
confidence: 78%
“…Finally the efficiency of the diffraction grating itself could not be estimated at this stage due to the several possible sources of loss in the whole spectrometer previously mentioned, but is expected to be high from the precise FDTD estimation. For comparison, other CDG spectrometers have an average efficiency of -3.2 dB, with a range from -5.0 dB to -1.6 dB, as claimed, 14,[19][20][21]24,25,29,30,[33][34][35] and have an average channel uniformity (over a band equivalent to 30 nm at 1550 mn) of 0.9 dB, with a range from 1.5 dB to 0.2 dB. 14,[19][20][21]24,25,29,30,[33][34][35] This places the present spectrometer within the state of the art for efficiency and at a high level for uniformity.…”
Section: Optical Testingmentioning
confidence: 78%
“…Similarly, on the 400 nm silicon waveguide platform 3-dB/cm waveguide losses at a wavelength of 3.8 μm were obtained [9]. Besides low-loss waveguides, functional components for spectroscopic sensing systems were also demonstrated [10], including planar concave grating spectrometers and arrayed waveguide gratings in the 2-2.5 μm [11] and 3.8-μm wavelength range [9]. The transmission spectrum of a silicon-on-insulator wavemeter (a wavelength demultiplexer circuit where the output channels intentionally overlap in order to accurately measure the wavelength of a laser line injected into the spectrometer through centroid detection) based on an arrayed waveguide grating is shown in Fig.…”
Section: Silicon-based Passive Waveguide Circuits For the Mid-infmentioning
confidence: 87%
“…The scalability of the heterogeneous integration of such photodetectors is illustrated in Fig. 4, showing the realization of a spectroscopic sensing system with 46 channels, covering the 1.5 to 2.3-μm wavelength range [11].…”
Section: Extending the Functionality Of Long-wavelength Photonicmentioning
confidence: 99%
“…Once they have been used solely in wavelength-division multiplexed communication networks [1,2]. In the course of time, their spectacular characteristics have expanded their application domain to spectroscopy and chemical sensors [3][4][5][6][7]. Many research groups have reported implementation of the AWGs on various platforms, such as silicon-on-insulator, silica-on-silicon and silicon-based polymers [8][9][10].…”
Section: Introductionmentioning
confidence: 99%